City of dreams : a novel - Winslow, Don, 1953- (William Morrow, an imprint of HarperCollinsPublishers, 2023)
On the losing side of a bloody East Coast crime war, Danny Ryan is now on the run. The Mafia, the cops, the FBI all want him dead or in prison. With his little boy, his elderly father and the tattered remnants of his loyal crew of soldiers, he makes the classic American migration to California to start a new life. But the Feds track him down and want Danny to do them a favor that could make him a fortune or kill him. And when Hollywood starts shooting a film based on his former life, Danny demands a piece of the action and begins to rebuild his criminal empire. Then he falls in love ... with a beautiful movie star who has a dark past of her own. As their worlds collide in an explosion that could destroy them both, Danny Ryan has to fight for his life in a city where dreams are born -- or where they go to die.